Disease Progression in Charcot–Marie–Tooth Disease Related to MPZ Mutations: A Longitudinal Study. Issue 3 (28th October 2022) - Fridman, Vera; Sillau, Stefan; Bockhorst, Jacob; Smith, Kaitlin; Moroni, Isabella; Pagliano, Emanuela; Pisciotta, Chiara; Piscosquito, Guiseppe; Laurá, Matilde; Muntoni, Francesco; Bacon, Chelsea; Feely, Shawna; et al.
Abstract : Objective: The paucity of longitudinal natural history studies in MPZ neuropathy remains a barrier to clinical trials. We have completed a longitudinal natural history study in patients with MPZ neuropathies across 13 sites of the Inherited Neuropathies Consortium. Methods: Change in Charcot–Marie–Tooth Examination Score (CMTES) and Rasch modified CMTES (CMTES‐R) were evaluated using longitudinal regression over a 5‐year period in subjects with MPZ neuropathy. Data from 139 patients with MPZ neuropathy were examined. Results: The average baseline CMTES and CMTES‐R were 10.84 (standard deviation [SD] = 6.0, range = 0–28) and 14.60 (SD = 7.56, range = 0–32), respectively. A mixed regression model showed significant change in CMTES at years 2–5 (mean change from baseline of 0.87 points at 2 years, p  = 0.008). Subgroup analysis revealed greater change in CMTES at 2 years in subjects with axonal as compared to demyelinating neuropathy (mean change of 1.30 points [ p  = 0.016] vs 0.06 points [ p  = 0.889]). Patients with a moderate baseline neuropathy severity also showed more notable change, by estimate, than those with mild or severe neuropathy (mean 2‐year change of 1.14 for baseline CMTES 8–14 [ p  = 0.025] vs −0.03 for baseline CMTES 0–7 [ p  = 0.958] and 0.25 for baseline CMTES ≥ 15 [ p  = 0.6897]). The progression in patients harboring specific MPZ mutations was highly variable. Interpretation: CMTES is sensitive to change over time in adult patients with axonal but not demyelinating forms of MPZ neuropathy. Change in CMTES was greatest in patients with moderate baseline disease severity. These findings will inform future clinical trials of MPZ neuropathies. ANN NEUROL 2023;93:563–576